Determinants of Household Migration: A Comparative Study by Race and Poverty Level - Kaluzny, Richard L. (The Review of Economics and Statistics, 1975)
M IGRATION studies using aggregate data IYL have noted the importance of differences in economic opportunity between areas on migration flows (Greenwood, 1969; Bowles, 1970; Fabricant, 1970). Studies using survey data have provided a more detailed profile of the characteristics identifying migrants, but have not incorporated the effects of economic incentives as fully as aggregate studies. Both approaches have noted significant differences in migration behavior among race or age groups, but neither has generated results which can be readily generalized to other groups of interest such as the poor. Recent interest in anti-poverty policies and income maintenance programs directed toward the poor suggest the need for explicit analysis of this group. The objective of this study is to examine the effects of economic incentives on migration for households grouped first by race and then by poverty level. The data, covering annual observation periods 1968-1969 and 1969-1970, focuses on households headed by persons less than fortyfive years old who are in the labor force at the beginning of an observation period (Institute for Social Research, 1970). The model takes the basic form